Explaining Ethical Consumption Behaviour in Europe: Empirical Evidence from 19 countries - Себастиан Коос (Journal of Economic Sociology, 2010)
This research is devoted to ethical consumption understood as the buying or not buying of goods, for ethical, political or environmental reasons. This type of consumption is studied from the moral economy perspective. The data used here for analysis is the European Social Survey (ESS) of 2002/ 2003. In a cross section of 19 European countries the author explores determinants of self-reported ethical, political and ecological consumption. On the individual level he finds that especially education and values concerned with environmental care are important explanations for ethical buying or boycotting behaviour. Country level differences in ethical consumption can to a large degree be explained by the affluence of countries.потребление